Modern Technologies for Creating the Thin-Film Systems and Coatings 2017
DOI: 10.5772/66040
|View full text |Cite
|
Sign up to set email alerts
|

Close‐Spaced Sublimation (CSS): A Low‐Cost, High‐Yield Deposition System for Cadmium Telluride (CdTe) Thin Film Solar Cells

Abstract: Semiconductors are the key materials in many of our modern day devices, such as sensors, integrated circuits, energy harvesting devices, optoelectronics and so on. However, apart from two known elemental semiconductors that are silicon and germanium, we have been using many of the synthesized ones since the microelectronic revolution known as invention of transistor. Numerous compound semiconductors since then have been synthesized, grown, deposited or simply fabricated by numerous processes in the scientific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This suggests an incomplete treatment process in specific temperatures (below 390 °C) and over-heating when annealing temperatures >410 °C applied. Since, in the CSS deposition process, films go through a transition temperature (600 °C) and experience the highest possible grain nucleation stage, the thickness will not increase significantly during treatment [44,45]. From Figure 5.…”
Section: Optical Analysismentioning
confidence: 99%
“…This suggests an incomplete treatment process in specific temperatures (below 390 °C) and over-heating when annealing temperatures >410 °C applied. Since, in the CSS deposition process, films go through a transition temperature (600 °C) and experience the highest possible grain nucleation stage, the thickness will not increase significantly during treatment [44,45]. From Figure 5.…”
Section: Optical Analysismentioning
confidence: 99%
“…On the one hand, higher and controlled growth temperature improves the deposition rate; it also determines the superiority of junction quality. [96] CSS technique is very well known for the deposition of CdTe deposition for decades [97] and has also been successfully applied for deposition of Sb 2 Se 3 , which obtained a decent PCE. [98] CSS approach has yet rarely been applied for Sb 2 S 3 deposition.…”
Section: Sb 2 S 3 Deposition Strategiesmentioning
confidence: 99%
“…The distance of source and substrate in the CSS method was fixed at 1 mm (Figure 1c) to reduce the loss possibility or undesired mass scattering during the sublimation process [16]. Other reports are available presenting the detailed strategies used in the CSS method [5]. The deposition rate R is an inverse function of source temperature T SO and Boltzmann constant k, as shown in Equation (1) [6].…”
Section: Experimental Procedures 21 Deposition Of Cdte Thin Filmmentioning
confidence: 99%
“…However, there is an extremum, namely, the glass transformation temperature (Tg = 560 • C) to be considered during the thin-film deposition on the flexible glass substrate [4]. As a result, regulating the deposition pressure during the sublimation process is an effective way to further improve thin-film specifications [5]. Related earlier studies demonstrated the effect of sublimation pressure on the mechanism of the CSS deposition system on normal borosilicate (1.1 to 3 mm thick) glass.…”
Section: Introductionmentioning
confidence: 99%